PENGARUH POLITICAL CONNECTION DAN BOARD GENDER DIVERSITY TERHADAP TAX AVOIDANCE - Muhammad Fikri Raharjo (2021)
This study aims to determine whether there is an effect of political connection and board gender diversity on tax avoidance. This study also uses control variables, namely leverage, size and return on assets. Tax avoidance as an independent variable is measured using two measurements, namely TA (ABTD) and TA (ETR). The political connection variable is projected by its presence on the board of commissioners and directors who have political relations, while the board gender diversity variable is projected by the presence of a women's board on the board of directors and commissioners. This study uses secondary data from the annual reports and financial statements of BUMN companies that have been audited by an independent auditor from 2017-2019. The total sample obtained was 33 state-owned companies. While the method used is multiple linear regression analysis. This study uses Stata version 12. The results of this study indicate that political connection has no effect on tax avoidance. Board gender diversity in the first measurement model TA (ABTD) has no effect whereas in the second measurement TA (ETR) there is a significant negative effect on board gender diversity on tax avoidance.